Koncept dela v kabinetu za glavkom - Trglec, Andrejka; Kurelac, Zlatko (Obzornik zdravstvene nege, 1984)
Increased intraocular pressure or glaucoma is a relatively frequent disease, occurring especially in elderly, of about 2% of individuals above 40 years of age who are already affected, more than a half are quite ignorant of their condition. Intraocular pressure may be due to an eye disease, or may result from inadequate production and drainage of the aqueous humor. In the Glaucoma Unit of the Department of Eye Diseases Maribor, about 1,000 cases of glaucoma have been registered so far. The patients have followup examinations every three or four months. Therapy is prescribed for each patient separately, depending on his condition at the time of examination.